Stability and physical properties of model macro- and nano/submicron emulsions containing fenugreek gum. (December 2016) - Kaltsa, Olga; Spiliopoulou, Neolea; Yanniotis, Stavros; Mandala, Ioanna
Abstract: Nanoemulsions were made in two steps. Firstly, a less viscous, primary O/W emulsion was prepared using ultrasounds. In those emulsions, only whey protein isolate was used as an emulsifier, whereas the oily phase was olive oil. A stabilizer, fenugreek gum, was incorporated afterwards in the primary formulations resulting in the secondary emulsions of increased viscosity. Oil amount changed and its decrease from 20 to 5% wt led to a reduced average droplet size and polydispersity index values in the primary emulsions. Nanoemulsions with the lowest polydispersity were produced at a high sonication time treatment of 12 min. Their droplet size was ∼200 nm. They showed increased viscoelastic properties and consistency leading to significantly increased stability compared to their coarse secondary emulsions produced by high shear mixing. Even the formulations with the lowest olive oil content investigated, 2.5% wt, presented an improved stability during a long-term storage of six months. Graphical abstract: Highlights: Low oil content macro and nanoemulsion models were prepared containing fenugreek gum. Droplet size decrease enhanced the rheological properties of nanoemulsions. Nanosized droplets are mostly appreciated for emulsions with the lowest oil content (2.5%).